From Ideals to Action: Promoting Peace Values in an Islamic Boarding School Committed to Activism - Rosyad, Rifki; Dian, Dian (FISIP UIN SGD Bandung, 2025)
The values of peace education have consistently been implemented in public educational institutions and peace communities such as schools, Islamic boarding schools, and non-governmental peace organizations (NGOs) so that studies on the implementation of peace values in other educational institutions, such as pesantren-based schools, have become rare. This article seeks to fill this gap by examining the performance of peace values in Islamic boarding schools in Indonesia, focusing on Peaceantren Welas Asih (PWA) of Garut, West Java. The qualitative research method collects observation data, interviews, and document reviews. This research found a process of implementing the values of peace in PWA using the 12 values of peace as a basis. This was then revealed in activities encouraging PWA students to become peacemakers. The program I Massage Card, Positive Discipline, and Peace Camp is part of PWA's efforts to instill peace values that have proven successful. In addition, cooperation between schools and parents of students helps these programs run successfully. This study concludes that developing pesantren-based schools is not only concerned with modernizing Islamic education. Still, the social-community role is far from that, especially the creation of human resources aware of peace. Contribution: The study emphasizes the importance of collaboration between schools and parents in reinforcing peace education efforts. This insight can guide other institutions in developing partnerships that support educational goals.